Sectoral real exchange rates and manufacturing exports: A case study of Latin America (2021)
Standard theory considers the real exchange rate (RER) as an export determinant. A common limitation of cross-country evidence is the use of effective (REER) or bilateral (BRER) RER indices, both of which have the same values across sectors. The novel contributions of this paper are to propose a variety of goods trade model, to exploit exchange rate variations across sectors by constructing a unique sectoral bilateral RER index (SBRER) for 12 Latin American countries, 21 sectors and 38 trade partners, and to estimate empirically the effect of SBRER movements on Latin American manufacturing exports during 2001-2018. The obtained results show that the SBRER is a statistically significant determinant of aggregate manufacturing exports, whereas the REER coefficient has an unexpected sign and the BRER appears not to be significant. Moreover, sectoral export elasticities indicate that in Latin America mainly low-technology sectors are affected by SBRER movements. Overall, these findings make evident that it is important to consider sectoral heterogeneity regarding trade partners and production costs when estimating RER export elasticities from a macroeconomic perspective and they provide new evidence on the effect of RER movements on Latin American exports.